EFFECT OF ADDING RED GINGER (Zingiber officinale rosc) JUICE ON THE PHYSICAL AND ORGANOLEPTIC QUALITY OF LAMB MEAT DRIVE - Devika Sari; Warisman, Warisman (Journal of Innovation Research and Knowledge, 2024)
This study aims to determine the physical and organoleptic quality of lamb jerky marinated using red ginger juice with different concentrations in each treatment. The research design used was a Completely Randomized Design (CRD) consisting of 4 treatments and 5 replications. The treatments included: Without red ginger (P0) as a control, Marinated with 10% red ginger juice (P1), Marinated with 15% red ginger juice (P2), and Marinated with 20% red ginger juice (P3). Physical test parameters include water holding capacity, pH, and cooking loss. Meanwhile, organoleptic test parameters include color, taste, aroma and texture. The results of physical tests in this study showed that the treatment had a very significant effect (P<0.01) on water holding capacity, pH and cooking loss. Meanwhile, the organoleptic test results showed that the treatment had a very real influence (P<0.01) on color and texture, but the taste variable in the organoleptic test showed that the treatment did not have a real influence (P>0.05). Marinating using red ginger juice can provide a level of acceptance of the organoleptic properties of lamb jerky, especially in color, aroma and texture